Achieving Whole Health: A Preliminary Study of TCMLH, a Group-Based Program Promoting Self-Care and Empowerment Among Veterans. (April 2022) - Abadi, Melissa; Richard, Bonnie; Shamblen, Steve; Drake, Connor; Schweinhart, April; Bokhour, Barbara; Bauer, Rachel; Rychener, David
Objective: An emerging literature suggests patients with chronic illnesses can benefit from integrated, person-centric approaches to health care, including group-based programs. However, much of the research in this area is disease specific. The objective of this study was to collect preliminary evidence on the efficacy of Taking Charge of My Life and Health (TCMLH), a Whole Health group-based program that emphasizes self-care and empowerment on the overall health and well-being of veterans, a population burdened with high rates of multiple chronic conditions. Method: Self-reported outcomes, including standardized survey measures, were collected at pretest, posttest, and 2-month follow-up from 77 participants across 15 groups at four VA sites. Random intercept mixed-model regressions were used to analyze data. Results: Results from this initial study showed high satisfaction with the program and facilitators, and high attendance. There were significant pre–post gains in self-care attitudes and behaviors, patient motivation, meaning and purpose, mental health, perceived stress, goal progress, and goal-specific hope. Outcomes were maintained at 2-month follow-up for patient motivation, perceived stress, goal-specific hope, and goal progress. Significant gains were observed in health care empowerment and physical health from pretest to follow-up. Conclusions: Preliminary findings support the efficacy of TCMLH, a Whole Health group-based program that emphasizes patient empowerment, self-care practices, and peer support. Future research priorities include a rigorous evaluation with a larger sample size and control group to assess effectiveness.